Online news regarding the spread of the omicron variant in Southeast Asia - Rulinawaty, Rulinawaty; Sjuchro, Dian Wardiana; Syahrial, Syahrial; Badollahi, Muh. Zainuddin; Hussain, Zulkifli (Faculty of Communications Science, Dr. Soetomo University, 2022)
Cases of Omicron-type Covid-19 have increased substantially worldwide. With the opening of the Omicron 68 case as of 30 December 2021, Indonesia has become the fourth largest country in Southeast Asia in terms of Covid cases. Singapore is in the first place, with 134 Omicron instances. This study aimed to find online news discourse regarding the spread of the Omicron variant in Southeast Asia. The method used in this research is van Dijk's Critical Discourse Analysis on online news via Kompas.com, news.abs-cbn.com, and channelnewsasia.com during December 2021. This study concludes that the three media reported the spread of the Omicron variant in the text dimension and tried to bring up vaccination efforts. In the dimension of social cognition, ensuring public health for the sake of survival is the ideology that is built. In the context dimension, the social context is built by providing equal opportunities to all people in getting the right to get vaccinated so that matters relating to health issues also have an impact on the economic aspect in line with the national economic recovery.